The business of armaments Armstrongs, Vickers and the international arms trade, 1855-1955 - Spear, Joanna 1961- (Cambridge University Press, 2023)
How did Britain's most prominent armaments firms, Armstrongs and Vickers, build their businesses and sell armaments in Britain and overseas from 1855 to 1955? Joanna Spear presents a comparative analysis of these firms and considers the relationships they built with the British Government and foreign states. She reveals how the firms developed and utilized independent domestic strategies and foreign policies against the backdrop of imperial expansion and the two world wars. Using extensive new research, this study examines the challenges the two firms faced in making domestic and international sales including the British Government's commitment to laissez faire policies, prejudices within the British elite against those in trade, and departmental resistance to dealing with private firms. It shows the suite of strategies and tactics that the firms developed to overcome these obstacles to selling arms at home and abroad and how they built enduring relationships with states in Latin America, Asia, and the Middle East
Title from publisher's bibliographic system (viewed on 19 Jan 2023)
Keywords: Vickers (Firm : Great Britain) / History; William G. Armstrong, Whitworth and Company; Vickers Limited; Geschichte 1855-1955; Arms transfers / Great Britain / History; Weapons industry / Great Britain / History; International trade / Great Britain / History; Imperialism / History; Rüstungsindustrie; Rüstungsexport; Großbritannien